Risk, uncertainty, crises management and public intervention in agriculture - Fabian Capitanio (Italian Review of Agricultural Economics (REA), 2022)
limate variability and extremes, socio-economic conditions, crisis and market shocks are among the main factors determining risk in the agricultural sector. Drought, heat stress, flood, market volatility among the others, have caused heavy losses in the recent past and both the occurrence and intensity of these extremes are expected to increase in the coming decades. Emerging and re-emerging diseases represent a serious concern for the future of agriculture. Here, we provide a synthetic overview of the theoretical framework that could lead public intervention in this specific field and discuss measures that have been taken to reduce economic losses for Italian farmers. We also tried to highlight the difference between risk and uncertainty that in a new global scenario will substantially characterize the reliability of empirical analyses in this complex research field.
Keywords: Q14; G18; G22; G32; 330; Risk Management In Agriculture; green portfolio; public support; risk vs uncertainty